2018
DOI: 10.18632/oncotarget.26355
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M is overexpressed in skin squamous-cell carcinoma and promotes tumor progression

Abstract: Cutaneous squamous cell carcinoma (cSCC) is the second most common keratinocyte malignancy and accounts for 20% of skin cancer deaths. Cancer is closely related to inflammation, but the contribution of the tumor microenvironment to cSCC development is poorly understood. We previously showed that oncostatin M (OSM), a cytokine belonging to the IL-6 family, promotes normal keratinocyte proliferation and migration, skin inflammation, and epidermal hyperplasia, both in vitro and in vivo. Here, we show that OSM is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 58 publications
4
20
0
Order By: Relevance
“…These initial data prompted us to characterize OSM involvement in keratinocytes. Here, OSM-enhanced motility is in accordance with previous in vitro studies 42,45,46 . Such tumor-promoting effects were regulated through JAK/STAT3 pathways 44,46 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These initial data prompted us to characterize OSM involvement in keratinocytes. Here, OSM-enhanced motility is in accordance with previous in vitro studies 42,45,46 . Such tumor-promoting effects were regulated through JAK/STAT3 pathways 44,46 .…”
Section: Discussionsupporting
confidence: 92%
“…OSM has been reported to promote a variety of pathologies, including skin inflammation, and various types of squamous cell carcinoma 35 , 36 , 42 44 . Integrated analyses using multiple data sets and pathway analysis platforms suggested that Oncostatin M signaling was activated early in UV-exposed skin and wounded skin as well as in cuSCC tumors (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…During inflammation, neutrophils are among the first phagocytes to infiltrate the tissue, mostly through CXC chemokine-mediated chemotaxis, and these cells predominate in the SCC invasive front ( Kruger et al, 2015 ; Simonneau et al, 2018 ; Khou et al, 2020 ). Progressive infiltration of tumor-associated neutrophils (TANs) was observed during the evolution of benign papillomas to established SCC lesions in a chemical carcinogenesis model, and tumor escape mostly involved the impairment of anti-tumor CD8 + T cell responses mediated by high arginase activity, production of reactive oxygen species (ROS), nitrite (NO), and the induction of PD-1 expression on CD8 + T cells ( Khou et al, 2020 ; Figure 1C ).…”
Section: Cellular Composition Of the Tumor Microenvironmentmentioning
confidence: 99%
“…The authors also demonstrated that hypoxia is crucial for N2 phenotype maintenance and tumor oxygenation can revert TANs phenotype toward N1 ( Mahiddine et al, 2020 ). Tumor-associated macrophages (TAMs) also represent a significant percentage of infiltrating phagocyte population in SCC ( Kambayashi et al, 2013 ; Amôr et al, 2018 ; Simonneau et al, 2018 ; Jiang et al, 2019 ), and specific depletion of these cells inhibited tumor growth ( Takahashi et al, 2009 ). The recruitment of monocytes into the SCC is mediated by CC chemokines such as CCL2 and, once in the TME, monocyte-derived macrophages are polarized toward a M1 or M2 phenotype ( Pettersen et al, 2011 ; Caley et al, 2020 ).…”
Section: Cellular Composition Of the Tumor Microenvironmentmentioning
confidence: 99%
“…A member of the IL6 family, it is an important inflammatory mediator in the skin ( Boniface et al, 2007 ) and is known to suppress differentiation in cooperation with other cytokines ( Rabeony et al, 2014 ). It also promotes proliferation of certain tumor cell types and progression of cutaneous and squamous cell carcinomas ( Simonneau et al, 2018 ). Like other cytokines, OSM signals through STAT1 and STAT3 as well as the mitogen-activated protein kinase pathway ( Dey et al, 2013 ), where sustained phosphorylation on tyrosine residues helps maintain transcriptional activity ( Andrés et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%